Research on the Obstruction Process of Rigid Netting Barriers toward Granular Flow - Yunyun Fan; Fengyuan Wu (Advances in Civil Engineering)
With the advantages of a simple structure and rapid construction, the rigid netting barrier (RNB) exerts a good obstruction effect on granular flow and is a common engineering measure used to prevent geological disasters in the form of granular flows. However, due to the limitations of current measuring and testing techniques, it is difficult to obtain an accurate measurement of the granular flow velocity and the impact force of granular flow on the mesh structures that are of primary concern in the design of protective structures. To study the characteristics of the obstruction process of RNBs toward granular flow, a typical impact experiment involving granular flow was numerically simulated by the discrete element method, and the correctness and effectiveness of the calculation method were also verified. On this basis, the discrete element method was applied to simulate the obstruction process affecting granular flow under different RNB setting conditions, and the calculation results clearly present the phenomena that occur during the obstruction process of RNBs toward granular flow, such as “run-up,” “overflow,” “passing-through,” and “grain-size segregation.” By analyzing the effects of these phenomena on the obstruction efficiency and the time history of the forces acting on the RNB, the rational setting of an RNB was further discussed. This study can provide a reference for the engineering application of RNB.